Diagnosis and management of bruxism. A literature review - Agnieszka Góra; Gustaw Laskowski; Piotr Węgrzyn; Konstancja Węgrzyn; Anna Salińska; Marcin Wasilewski; Maciej Nowicki; Julia Skwara; Dawid Barański; Natalia Dąbrowska (Nicolaus Copernicus University in Toruń, 2024)
Bruxism, characterized by involuntary grinding or clenching of teeth, is a widespread condition with multifaceted implications for oral health, physical well-being, and quality of life. This comprehensive review aims to provide an in-depth study of bruxism, encompassing its definition, classification, etiology, pathophysiology, clinical manifestations, and consequences. Bruxism is classified based on its timing (sleep bruxism or awake bruxism). The etiology of bruxism is multifactorial, involving physiological factors such as central nervous system (CNS) pathways, sleep disorders, and occlusal factors, as well as psychological factors like stress, anxiety, personality traits and environmental factors including medications, substances, and stressors. Clinically, bruxism can result in various dental consequences, including tooth wear, fractures and damage to restorations, as well as temporomandibular disorders (TMDs) such as myofascial pain. These manifestations can negatively impact individual's oral health, physical well-being, and overall quality of life. Management strategies include behavioral and lifestyle changes, oral appliances, dental treatments for tooth damage, and, in certain instances, pharmacological interventions. While the current understanding of bruxism has advanced, further research is needed to fully elucidate its etiology, pathophysiology, and effective management strategies.